منهج الإمام عبد الحميد بن باديس في التربية والتعليم - محمد الصالح, منى (University of Eloued جامعة الوادي, 2017)
إن رجال الإصلاح من أمثال الإمام المحدد عبد الحميد بن باديس, إستطاع أن يبطل مخططات هذا العدو ويزرع الأمل واليقين, داخل أبناء أمته وطنه من خلال وسائل وأساليب مختلفة مكثفة من وضع حد لكل الأباطيل، ولعل من أبرز الوسائل والدروس التي قدمها في المساجد والمدارس والصحافة. وفي دراستي هذه تطرقت إلى المنهج الذي إتبعه الشيخ عبد الحميد بن باديس في التربية والتعليم وقد قسمت دراستي هده إلى ثلاثة فصول. كان ولابد أن نتطرق في الفصل الأول إلى عصر الشيخ الإمام بن باديس وهذا لدراسة الحالة السياسية والثقافية والاجتماعية وحياته الشخصية. أما الفصل الثاني, كان الحديث عن جهوده التربوية من خلال التطرق إلى ما قام به في مجال التدريس ومجهودات معتبرة أخرى. أما الفصل الثالث, فقد كان فيه صلب الموضوع وهنا نتطرق للإصلاحات التي قام بها الشيخ عبد الحميد بن باديس بعدها دراسة منهجية الامام في طرح المواضيع المختلفة والتي ساهمت في نجاح إصلاحاته. وفي الختام كانت لدي أجوبة لأهم الاشكاليات المطروحة في خاتمة هذه الدراسة يعقبها توضيح بعض الأفكار التي سعى إليها الإمام عبد الحميد بن باديس من خلال انجازاته The men of reform, such as the specific Imam Abdulhamid bin Badis, managed to nullify the schemes of this enemy and instill hope and certainty within the people of his nation through various means and methods of intensifying the end of all falsehoods and perhaps one of the most prominent means and lessons presented in mosques, schools and the press. In my study, I referred to the approach followed by Sheikh Abdul Hamid bin Badis in education and I divided this study into three chapters. In the first chapter, we should refer to the era of Sheikh Imam Ibn Badis, and this is to study the political, cultural and social situation and his personal life. The second chapter was talking about his educational efforts through addressing what he did in the field of teaching and other significant efforts. As for the third chapter, it was the crux of the subject and here we address the reforms carried out by Sheikh Abdul Hamid bin Badis, then study the methodology of the Imam in the introduction of various subjects, which contributed to the success of his reforms. In conclusion, I had answers to the most important problems presented at the conclusion of this study followed by clarification of some of the ideas sought by Imam Abdul Hamid bin Badis through his achievements
مذكرة ماستر تخصص دعوة واعلام
Keywords: : رجال الإصلاح، التربية والتعليم، الشيخ عبد الحميد بن باديس: Men of Reform, Education, Sheikh Abdul Hamid bin Badis